Dermatovenerological infections. (5th April 2023) - Fabri, Mario; Stary, Georg
Summary: In dermatology, infections caused by bacteria, viruses, fungi, and parasites play an important role. A large proportion of pathogen‐related infections of the skin and mucous membranes are transmitted sexually. All areas of infectious diseases and dermatovenerology are subject to highly exciting, dynamic change. This is driven by changes in the epidemiology of long‐established diseases, changes in the resistance of pathogens to anti‐infectives, recurrence of known pathogens, and the emergence of completely new pathogens. In this article, we address "resistance to anti‐infectives", "sexually transmitted infections", and "emerging viral infections", three core areas of dermatovenerology that will shape the field in the years to come.